Cranioplasty: Materials and Methods Review - A. V. Yarikov; A. P. Fraerman; V. A. Leonov; O. A. Perlmutter; S. E. Tikhomirov; A. V. Yaksargin; P. V. Smirnov (Креативная хирургия и онкология, 2020)
Reconstructive plastic surgery procedures — cranioplasty in particular — are finding their way into the current dayto-day neurosurgery practices. A defect in the skull bones leads not only to cosmetic defects and related psychological problems, but can also cause neurological disorders. Reconstruction of skull defects is considered an important neurosurgical stage of craniocerebral injury victims’ recovery. Currently, there are no clear established algorithms or timing for cranioplasty. This paper presents data on the history and stages of the development of reconstructive neurosurgery. The efficiency of treatment of the syndrome of the trephinated with cranioplasty has been proven. The key materials used to close the skull bones defects are presented and the requirements for the material used for closing cranial defects are described. Advantages and disadvantages of materials currently used — autograft bone, allograft bone, reperen, polyetherketone, polymethylmethacrylate, titanium, hydroxyapatite — are presented in detail. A separate section of the article is devoted to the methods of transplant modelling — 3D printing and stereolithography. This is followed by the stipulation of the key principles of cranioplasty.